Tempted - Cast, P. C.; Cast, Kristin (New York : St. Martins Griffith, 2009)
The friendship between Zoey and Stevie Rae is tested as they keep secrets from each other and face seductive immortals and mysterious, threatening forces.
Series numbering provided by cataloger.
Keywords: Redbird, Zoey (Fictitious character) -- Fiction; Vampires -- Fiction; Teenagers -- Fiction; Teenage girls -- Fiction; Good and evil -- Fiction; Tulsa (Okla.) -- Fiction; Fantasy fiction; Occult fiction